Economists as Wordly Philosophers - Shiller, Robert J.; Shiller, Virginia (Cultura Económica, 2018)
While leading figures in the early history of economics conceived it as inseparable from philosophy and the humanities, there has been a tendency especially in recent decades, towards its becoming an essentially technical field with narrowly specialized areas of inquiry. Certainly, specialization has allowed for great progress in economic science. However, recent events surrounding the financial crisis support the arguments of those who suggest the need to develop forums for interdisciplinary interaction and to aspire to a broader view of economics as a science.